PEMBELIAN TIDAK TERENCANA PADA HYPERMART : Studi Pada Giant Cinere Depok - Endy Setiawan, - (2019)
This research is a quantitative that aims to determine the effect of store atmosphere, store atmosphere and bonus packaging to impulse buying. Population in this research is visitor of Transmart Carrefour Cilandak. The variables used in this research are store atmosphere, influence discounts and bonus packagingas independent variable, then impulse buying as dependent variable.The sample size was taken 75 respondents, with non probability sampling method, especially purposive sampling. Data collection was done through questionnaires. In this research, three hypotheses will be tested using PLS (Partial Least Square) analysis tool.Based on the results of data processing with PLS (Partial Least Square) has the result that (1) Store Atmosphere has a significant influence on impulse buying with the coefficient value of 0,497. (2) influence sales promotion have no significant effect on impulse buying with the coefficient value of -0,007.. (3) attribute producthas a significant influence on impulse buying with the coefficient value of 0,420.